Development of a Multiple Intelligence-Based Learning Management Model for Elementary Schools - Mulyono, Rahmat; Rejokirono; Slamet Untung (EduBase : Journal of Basic Education, 2025)
Objective: This research aimed to (1) produce information about the components needed for the development of multiple intelligence-based learning management, (2) produce a model of multiple intelligence-based learning management, and (3) provide information on the model’s effectiveness. Novelty: The study offers a structured model of learning management specifically designed to integrate multiple intelligences, addressing the diverse abilities of students in elementary schools. Methods: The research involved three stages—preliminary study, model development, and testing—conducted in several provinces with tryouts in thirteen elementary schools, using data from headmasters and teachers collected through questionnaires, interviews, and observations, and analyzed descriptively. Results: The research produced a multiple intelligence-based learning management model characterized by materials and groupings tailored to students’ intelligences, thematic and active learning approaches, comprehensive evaluation, outing class activities, collaboration with parents and stakeholders, and visionary leadership. The model showed very good results, with content testing scoring 91.58% and applicability testing 92.20%. Conclusions: The findings demonstrate that the developed model is both effective and practical, offering a comprehensive framework for implementing multiple intelligence-based learning management in elementary schools.